THE IMPLEMENTATION OF PIONEER TEACHING CAMPUS (PTC) AS A FORERUNNER OF LITERACY AND NUMERACY LEARNING MOVEMENT AT ELEMENTARY SCHOOL - Fajar Setiawan; Sukamto (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
The focus of this research was to determine the implementation of Pioneer Teaching Campus (PTC) 2020 activities as a forerunner to driving literacy and numeracy learning at elementary schools. The type of this research was qualitative research with a narrative approach. The stages in this narrative research included (1) identification of phenomena to be studied, (2) determining participants allowing researchers to study the phenomena, (3) gathering information (experiences) from participants, (4) retelling information (experiences) from participants, (5) collaborating with participants, and (6) writing narratives based on information (experiences) from participants. The results showed that the implementation of PTC 2020 was very helpful for teachers in target schools, especially in literacy and numeracy learning since it was common for many teachers to be reluctant to carry out literacy and numeracy learning in their classes, even though literacy and numeracy programs had been promoted for a long time. Many factors caused this condition, ranging from age that affected motivation, teachers' understanding of literacy and numeracy learning, to the limited ability of teachers to use technology.